Partisipasi dan Kepuasan Petani Terhadap Pendamping Program Peremajaan Sawit Rakyat (PSR) di Kabupaten Bangka Tengah - Apriadi, Demsi; Agustina, Fournita; Evahelda (Universitas Medan Area, 2025)
One of the important factors that determines the success of PSR activities is farmer participation, without farmer participation, PSR activities will not be successful, because the role of farmers is as the main actor in the agricultural development program. In addition, the task of the assistant in this PSR can be used as evaluation material for farmer satisfaction in the performance of the assistant for the smallholder oil palm rejuvenation program, as well as to find out what factors or attributes must be improved for the assistance of the Central Bangka PSR program in an effort to improve the quality of service to oil palm farmers. The purpose of this study is to analyze the Level of Participation and Farmer Satisfaction with the Assistants for the Smallholder Oil Palm Rejuvenation Program (PSR) in Central Bangka Regency. This research was carried out in 10 Gapoktan spread across Central Bangka Regency from January to February 2024. The sample of this study was oil palm farmers who were members of the Gapoktan institution and had implemented the Smallholder Oil Palm Rejuvenation (PSR) program in Central Bangka Regency with a total of 80 farmers. The sampling technique for this study used probability sampling using the proportionate stratified random sampling method. The data analysis method used in this study uses the IPA (Importance Performance Analysis) and CSI (Customer Satisfaction Index) methods. The results of the study showed that the level of farmer participation in the People's Oil Palm Rejuvenation Program (PSR) in Central Bangka Regency was very high, namely 90.95% with a very high percentage of participation value. The Customer Satisfaction Index (CSI) on the performance or services that have been carried out by the People's Oil Palm Rejuvenation Program (PSR) Companions in Central Bangka Regency was 90.22% with the criteria of very satisfied